Dr. Anthony Fauci Shares Insights on His Career and Leadership of the NIAID - Michael M. Lederman; Neil Greenspan (Case Western Reserve University, 2024)
In this interview, Dr. Anthony Fauci, who was, until recently, the director of the National Institute of Allergy and Infectious Diseases at the National Institutes of Health, discusses the national response to the HIV/AIDS pandemic. He was the principal architect of the President's Emergency Plan for AIDS Relief, known as PEPFAR, that has saved millions of lives throughout the developing world by assuring access to life-saving antiretroviral therapies. In recent years, he's been the voice of our national response to SARS, Ebola, and COVID, and throughout this Dr. Fauci has led a large basic and translational immunology research laboratory, The Laboratory of Immunoregulation, which has revealed a trove of insights about HIV pathogenesis.